2010
DOI: 10.2495/islands100121
|View full text |Cite
|
Sign up to set email alerts
|

Rising sea level and long term sustainability of near-shore islands of the United Arab Emirates: an approach to establishing setback lines for Abu Dhabi

Abstract: In recent years an important infrastructural and human development focus for the United Arab Emirates has been along the shoreline of its northern coast fronting the Arabian Gulf. The Gulf itself is a large, warm, shallow semi-enclosed body of water with complex oceanography and geomorphological history. Its southern shores, including that of the northern UAE, are predominantly sandy. The value of present infrastructure, especially in the capital city Abu Dhabi, constructed on a number of natural and man-made … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…An extensive review of all the information pertaining to changing sea level in the Abu Dhabi region; including possible storm and tide surges, and probable highest significant waves; was completed by Garland (2010). In the review, he included global information from Pfeffer et al (2008), IPCC (2007) Garland's analysis confirmed that sea level change in the Arabian Gulf mirrors global eustatic change.…”
Section: Expected Sea Level Rise Along the Rak Coast Linementioning
confidence: 99%
See 3 more Smart Citations
“…An extensive review of all the information pertaining to changing sea level in the Abu Dhabi region; including possible storm and tide surges, and probable highest significant waves; was completed by Garland (2010). In the review, he included global information from Pfeffer et al (2008), IPCC (2007) Garland's analysis confirmed that sea level change in the Arabian Gulf mirrors global eustatic change.…”
Section: Expected Sea Level Rise Along the Rak Coast Linementioning
confidence: 99%
“…The difference between exposed sites and sheltered sites vary significantly. The expert sea level rise estimations are shown in Table 1, with the final expected flooding levels; including sporadic effects of storm and tide surges and highest significant waves; are detailed in Table 2 as per Garland's (2010) analysis.…”
Section: Figure 2 the Ras Al Khaimah And Al Hamra Village Coastline mentioning
confidence: 99%
See 2 more Smart Citations
“…The United Arab Emirates, located at the South-Eastern end of the Arabian Gulf, has invested greatly in development along its coastline. Many of these developments will be at risk from future sea level rise (Garland 2010). Going through a phase of rapid economic growth, the UAE is experiencing urban growth at an unprecedented pace.…”
Section: Introductionmentioning
confidence: 99%